2017
DOI: 10.1186/s12943-017-0622-y
|View full text |Cite
|
Sign up to set email alerts
|

Ion channels or aquaporins as novel molecular targets in gastric cancer

Abstract: Gastric cancer (GC) is a common disease with few effective treatment choices and poor prognosis, and has the second-highest mortality rates among all cancers worldwide. Dysregulation and/or malfunction of ion channels or aquaporins (AQPs) are common in various human cancers. Furthermore, ion channels are involved in numerous important aspects of the tumor aggressive phonotype, such as proliferation, cell cycle, apoptosis, motility, migration, and invasion. Indeed, by localizing in the plasma membrane, ion chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 104 publications
(95 reference statements)
0
28
0
Order By: Relevance
“…Recently, it was also highlighted that ion channels are quite promising targets in anticancer protocols. Ion channels are responsible for numerous cellular processes and their expression varies in different types of cancers 26,27 . In our study, an increase of expression of water channels and mitochondrial VDAC1 was determined, which can significantly support the cytotoxic and anticancer effect caused by EP and CaEP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was also highlighted that ion channels are quite promising targets in anticancer protocols. Ion channels are responsible for numerous cellular processes and their expression varies in different types of cancers 26,27 . In our study, an increase of expression of water channels and mitochondrial VDAC1 was determined, which can significantly support the cytotoxic and anticancer effect caused by EP and CaEP.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, an increase of expression of water channels and mitochondrial VDAC1 was determined, which can significantly support the cytotoxic and anticancer effect caused by EP and CaEP. The disruption of the channel functioning is an additional factor that may cause cell death 26,27 . Molecular dynamics study involving electropermeabilization effect on transmembrane water channels (aquaporins) demonstrated a significant effect of water self-diffusion during and immediately after the pulses 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study did not detect AQP6 in bovine mammary gland 44 . Ion channels and aquaporins were reported to be involved in cell proliferation, cell cycle progression, and cell migration, in response to different stimuli 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…During past decades, a number of studies have demonstrated the association between the activity of ion channels and the progression of different types of cancer, and considerable achievements have been made in understanding the role of ion channels in cancer (7,40,41). hERG1 has been reported to exhibit oncogenic properties, is often aberrantly expressed in cancer and has essential roles in numerous crucial cellular events (15,16).…”
Section: Discussionmentioning
confidence: 99%